Auto‐Crosslinked Rigid Foams Derived from Biorefinery Byproducts. Issue 16 (25th July 2018) - Tosi, Pierluigi; van Klink, Gerard P. M.; Celzard, Alain; Fierro, Vanessa; Vincent, Luc; de Jong, Ed; Mija, Alice
Abstract: A new macroporous foam‐like material is presented based on autocross‐linking humins, an industrial biorefinery byproduct. Humins foams are obtained by a simple heating process, without any pretreatment and with high control of morphology, porosity, and carbon content. Untreated humins have been characterized by GC, ultra‐performance liquid chromatography (UPLC), elemental analysis, and FTIR, whereas the mechanism of foaming was elucidated by a combination of thermal and rheological analyses. A preliminary screening of conditions was conducted to identify the parameters controlling this foaming process. A foam was produced in a controlled way with open and/or closed cells with cell diameters between 0.2 and 3.5 mm. Humins foams were characterized by Raman spectroscopy, FTIR, SEM, nitrogen adsorption, pycnometry, and mechanical tests. The results show that, based on humins, it is possible to obtain porous materials with controlled architectures and a range of parameters that can be tailored, depending on the foreseen applications. Abstract : The second life of a biorefinery byproduct : Humins as side‐stream industrial products can be converted to a carbonaceous macroporous rigid material by using a simple, straightforward thermal treatment. The mechanism of foaming has been revealed and the humins foams characterized. This promising material could represent the future of humins, with clear economic advantages for the entire biorefinery industry.